Notes On Weakly Separation Properties (Journal of the College of Basic Education, 2023)
In this work , we obtain the definitions to  - T 1/4 and  - T 1/2 , also we study the relationship between  - T 0 ,  - T 1/4 ,  - T 1/2 and  - T 1 , andgive the relation between them and the ordinary separation axioms withexamples .